Participation in a remote hearing in administrative court proceedings - Marcin Adamczyk (Journal of Modern Science)
Objectives The article is devoted to the topic of remote hearings in administrative court proceedings in Poland. It presents how technological development and the need for digitalization affect the justice system, in particular in the context of administrative court processes, in which the use of digital tools can significantly reform existing procedures. The current state of legal regulations regarding remote hearings was presented, emphasizing the need to update them and adapt them to dynamically changing technological conditions. The aim of the article is not only to discuss the applicable legal regulations, but also to propose directions for their development. In particular, it was proposed to introduce provisions enabling participation in remote hearings outside court premises. It was also pointed out that there is a risk that insufficiently precise provisions may remain without practical application if appropriate legislative steps are not taken and organizational. In conclusion, the article proposes the adoption of remote hearings as the default mode in judicial and administrative proceedings, emphasizing that this solution can speed up proceedings and increase access to court, and thus gain citizens' trust in the justice system.